PHARMACOLOGICAL EFFICIENCY OF STATINS AND L-NORVALIN AT AN ENDOTOXIN-INDUCED ENDOTHELIAL DYSFUNCTION - Inna Ivlitskaya; Michael Korokin; Aleksey Loktionov (Belgorod National Research University, 2016)
In the animals with endotoxin-induced endothelial dysfunction there were imbalance of contractile response of vessels wall observes when carrying out functional tests, increase of coefficient of endothelial dysfunction, decrease in contractility of a myocardium, activation processes of peroxidation of lipids and decreased activity of antioxidant systems, level of stable metabolites of nitrogen oxide. On extent of decrease in corrective effects on indicators of functional activity of a vessel wall, contractility of a myocardium, oxidatic indicators and level of stable metabolites of nitrogen oxide are studied preparations settle down in the following sequence: L-norvalin and rozuvastatin (coefficient of endothelial dysfunction - 1,2±0,1) → Lnorvalin and simvastatin (coefficient of endothelial dysfunction - 1,5±0,1) → rozuvastatin (coefficient of endothelial dysfunction - 1,6±0,1) → L-norvalin (coefficient of endothelial dysfunction - 1,7±0,2) → symvastatin (coefficient of endothelial dysfunction - 2,0±0,2).